1986
DOI: 10.4319/lo.1986.31.1.0034
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the rate of release of phosphorus by zooplankton on the P: C ratio in the food supply, as calculated by a recycling model1

Abstract: In two enclosure experiments, Daphnia pulex ingested cryptophytes, bacteria, and probably detritus particles. The specific clearance rate of the zooplankton increased when the concentration of food decreased. The P : C ratio of the food also increased. More than 92% of the particulate phosphorus was located in the living cells (algae and bacteria); the detritus was practically phosphorus-free. The specific release rate of phosphorus estimated for the daphnids by use of the recycling model increased as the P : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
133
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 14 publications
8
133
0
Order By: Relevance
“…Contribution of metazoan plankton to nutrient supply for phytoplankton. Olsen et al 1986; den Oude and Gulati 1988; Urabe 1993a), although the P release rate is at the lower end of the range due to food conditions with a low P content relative to C and N. During our study, the ratio of N to P released by the zooplankton was usually far higher than the scstonic N:P ratio and ranged from 19 to 123. Urabe (1993a) found that in a small pond where large daphnids dominated, the N:P ratio of food was the most important factor affecting the N:P release ratio of zooplankton.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Contribution of metazoan plankton to nutrient supply for phytoplankton. Olsen et al 1986; den Oude and Gulati 1988; Urabe 1993a), although the P release rate is at the lower end of the range due to food conditions with a low P content relative to C and N. During our study, the ratio of N to P released by the zooplankton was usually far higher than the scstonic N:P ratio and ranged from 19 to 123. Urabe (1993a) found that in a small pond where large daphnids dominated, the N:P ratio of food was the most important factor affecting the N:P release ratio of zooplankton.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the accumulation efficiency was higher for P than for N in the months when the N:P ratio of seston was higher than that of the zooplankton. Olsen et al (1986) also showed that more assimilated P was accumulated into body tissue when food with a higher P:C ratio was supplied. Similarly, Urabe (1993a) indicated that the fraction of the eliminated N used for net production was higher than that of P when zooplankton were given food with a low N:P ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The growth can be calculated as the ingestion -release (Olsen et al 1986;DeMott et al 1998), where the release includes defecation, excretion (C and P), and respiration (for C). The gross growth efficiency (GGE) was calculated as growth divided by the ingestion, and the net growth efficiency (NGE) was calculated as growth divided by absorption.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, some studies have found that certain zooplankton species exhibit a relevant temporal elemental variation (Main et al 1997;DeMott et al 1998;Villar-Argaiz et al 2002;Boersma and Kreutzer 2002;DeMott et al 2004). For these species, the direct application of nutrient recycling models (Olsen et al 1986) based on the assumption of strict elemental composition is inaccurate. Therefore, there is a need for elucidating why the stoichiometric composition is more (or less) strict for distinct species.…”
mentioning
confidence: 99%